1996
DOI: 10.1159/000196528
|View full text |Cite
|
Sign up to set email alerts
|

Release of Endothelin-1 into Rat Airways following Sephadex-Induced Inflammation; Modulation by Enzyme Inhibitors and Budesonide

Abstract: The intratracheal (i.t.) instillation of Sephadex beads into the rat induced inflammation and a 30-fold increase in the endothelin-1-like immunoreactivity (ET-1-LI) of broncho-alveolar lavage fluid. The levels were highest 24 h after the instillation and had declined significantly after 48 h. At a dose of 1 mg kg-1 i.t., the glucocorticosteroid budesonide almost abolished this response. Phosphoramidon, which inhibits neutral endopeptidase, an enzyme reported to degrade ET-1 and also to inhibit the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
4
0

Year Published

1996
1996
2004
2004

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 17 publications
2
4
0
Order By: Relevance
“…Instillation of Sephadex induced a great increase of ET-1-LI concentration in BALF, in agreement with previous results (Andersson et al 1996). In contrast, there was no detectable increase in ET-1-LI content in Table 1 Values for ET-1-LI (pmol L −" ), cell counts (10' mL −" ) and protein concentration ( µg mL −" ) in BALF in the rats pretreated with vehicle or bosentan (p.o.)…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Instillation of Sephadex induced a great increase of ET-1-LI concentration in BALF, in agreement with previous results (Andersson et al 1996). In contrast, there was no detectable increase in ET-1-LI content in Table 1 Values for ET-1-LI (pmol L −" ), cell counts (10' mL −" ) and protein concentration ( µg mL −" ) in BALF in the rats pretreated with vehicle or bosentan (p.o.)…”
Section: Discussionsupporting
confidence: 93%
“…There is also a marked influx of inflammatory cells, mainly eosinophils, into the airways and lung parenchyma. In previous works we have found that there is a large but transient increase in ET-1-LI content in BALF ; this increase parallels the development of the inflammatory reaction (Andersson et al 1996). We have therefore hypothesized that ET-1 could be mediating part of the observed inflammatory response.…”
mentioning
confidence: 77%
“…This type of reaction, which is mediated by immune-complex deposition, could induce a particular type of lung inflammation with a marked neutrophil infiltration and activation leading to a neutrophil-dependent lung injury. A similar release of ET was observed in another model of lung inflammation where large amounts of ET were detected in rat BAL fluid following intratracheal instillation of Sephadex beads (28). Enhanced intrapulmonary ET-1 production and increased pulmonary pre-pro ET-1 mRNA expression were also observed in rats with idiopathic pulmonary hypertension (29).…”
Section: Discussionsupporting
confidence: 73%
“…A well‐known method to study early eosinophilic inflammation in airways is tracheal instillation of Sephadex (Andersson et al 1992). During this kind of inflammation the concentration of endothelin‐1 in broncho‐alveolar fluid has been shown to be increased 30 times with its peak at 24 hr (Andersson et al 1996). It has been suggested that endothelin‐1 is paracrine in the airways during inflammation and hence may contribute to airway hyperreactivity.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, a number of studies have revealed that endothelin‐1 levels are significantly elevated in broncho‐alveolar lavage fluid and in plasma during asthmatic attacks (Vittori et al 1992; Michael & Markewitz 1996). Moreover, intratracheal instillation of Sephadex has been shown to create an eosinophilic airway inflammation with increased endothelin‐1 levels in broncho‐alveolar fluid (Andersson et al 1996) and that this elevation is preceded by a rapid entothelin‐1 mRNA synthesis (Finsnes et al 1998). These studies have suggested that this peptide plays an important role in the initial phase of an eosinophilic airway inflammation.…”
mentioning
confidence: 99%